Ballistic Performance of Natural Fiber Based Soft and Hard Body Armour- A Mini Review - Naveen, J.; Jayakrishna, K.; Hameed Sultan, Mohamed Thariq Bin; Amir, Siti Madiha Muhammad (Frontiers in Materials, 2020)
Increase in awareness towards utilization of eco-friendly materials, encouraged the researchers to find a sustainable alternative to synthetic fibers for different engineering applications. High performance Kevlar fabrics are widely used in ballistic applications such as bullet proof helmets, vest, and other armour systems. Ballistic impact produces shock waves which may cause severe trauma injuries to the soldiers. Kevlar fabric based armour system provides acceptable range of protection to the soldiers. However, disposal of Kevlar affects the eco system and pollutes the environment. Replacing Kevlar fabric in the protective structures with an eco-friendly light weight material, together with an improved kinetic energy absorption and dissipation has become an interesting approach to enhance the ballistic performance of the composite panels. This mini review addresses the effect of adding different natural fibers on the ballistic performance of soft and multilayered hard body armour systems. Many researchers explored the possibility of utilizing eco-friendly natural fibers (Kenaf, Cocos nucifera sheath, Malva, rami, curaua, bagasse, jute, bamboo) as an alternate material to Kevlar fabric in the armour system and reported that natural fibers can act as a potential reinforcement in the ballistic structures